2010
DOI: 10.1007/s10577-010-9137-8
|View full text |Cite
|
Sign up to set email alerts
|

Inheriting nuclear organization: can nuclear lamins impart spatial memory during post-mitotic nuclear assembly?

Abstract: Cell type and tissue architecture correlate with genome organization in higher eukaryotes, and structural nuclear landmarks are faithfully transmitted from one cell generation to the next. However, how nuclear components find their place in the nucleus after mitosis is still a matter of debate. As the major structural proteins within nuclei, the nuclear lamins are good candidates to re-establish nuclear compartments following mitosis. Human cells with reduced expression of the major B-type lamin protein, lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 55 publications
(94 reference statements)
0
25
0
Order By: Relevance
“…65 Recently it was demonstrated that lamin B1 maintains the functional plasticity of nucleoli 66 and participates in the post-mitotic structural reorganization of the nucleus and nucleoli. 67 In correlation with these conclusions, DNA sequencing of the nucleolus-associated chromatin domains revealed chromatin loci specifically associated with either the nucleolus or the nuclear envelope. 63 Interestingly, the reorganization of the nuclear envelope after mitosis is achieved with the same timing as nucleolar assembly.…”
Section: Outlook and Perspectivesmentioning
confidence: 69%
“…65 Recently it was demonstrated that lamin B1 maintains the functional plasticity of nucleoli 66 and participates in the post-mitotic structural reorganization of the nucleus and nucleoli. 67 In correlation with these conclusions, DNA sequencing of the nucleolus-associated chromatin domains revealed chromatin loci specifically associated with either the nucleolus or the nuclear envelope. 63 Interestingly, the reorganization of the nuclear envelope after mitosis is achieved with the same timing as nucleolar assembly.…”
Section: Outlook and Perspectivesmentioning
confidence: 69%
“…To further validate the contribution of compromised NE integrity to the mitotic phenotypes induced by TGFβ, we selected LaminB1, a major determinant of nuclear shape and size with a dual role in regulating cytokinesis, spindle matrix and chromatin condensation (Gruenbaum and Foisner, 2015; Guttinger et al, 2009; Hayashi et al, 2016; Martin et al, 2010; Tsai et al, 2006; Verstraeten et al, 2011), for more detailed analysis. TGFβ suppressed Lamins A and B1 proteins in MCF10A, SKBR3 as well as CDβgeo cells, whereas its removal restored the levels of Lamins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, LaminB1, suppressed by TGFβ and SNAIL, plays an important role in cytokinesis, spindle assembly and chromatin condensation (Funkhouser et al, 2013; Hayashi et al, 2016; Martin et al, 2010; Tsai et al, 2006; Verstraeten et al, 2011). Disruption of LaminB1 causes cause nuclear blebbing (Funkhouser et al, 2013), and cytokinesis failure leading to BN and MN cells (Funkhouser et al, 2013; Hayashi et al, 2016; Martin et al, 2010; Tsai et al, 2006; Verstraeten et al, 2011), thus, phenocopying the effects of TGFβ. Accordingly, restoring LaminB1 partially rescues the mitotic abnormalities induced by TGFβ suggesting that additional NE components suppressed by TGFβ are also likely to contribute to the cytokinesis and mitotic defects observed in cells undergoing EMT.…”
Section: Discussionmentioning
confidence: 99%
“…A careful biochemical analysis of these nuclear sub-fractions may provide further insights on these potential interactions with Lamin B2 required for the correct maintenance of CTs in a manner consistent with gene density. Alternatively, the decision to place chromosomes in unique nuclear locations is likely to be initiated during mitosis, where Lamins regulate chromosome segregation (Martin et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Laminopathies are a group of diseases due to mutations in Lamins, which show altered nuclear shapes, gene expression, and chromatin organization (Burke and Stewart 2002; Taimen et al 2009). Both A- and B-type Lamins are involved in wide range of cellular processes such as replication, transcription, cell division, DNA damage repair, differentiation, and senescence (Butin-Israeli et al 2015; Martin et al 2010; Shimi et al 2011; Shumaker et al 2008; Spann et al 2002; Swift et al 2013; Tang et al 2008). Furthermore, Lamins exhibit cell-type-specific expression levels and function (de Las Heras et al 2013; Swift et al 2013; Yang et al 2011).…”
Section: Introductionmentioning
confidence: 99%